High-intensity focused ultrasound (HIFU) versus deep brain stimulation (DBS) for refractory tremor: team DBS - Flávia de Paiva Santos Rolim; Denise Maria Menezes Cury Portela (Arquivos de Neuro-Psiquiatria)
Deep brain stimulation (DBS) has been widely accepted as a powerful tool capable of suppressing tremor by modulating the neuronal circuitry, with long-term adaptability and a profile of low adverse effects. It has been the primary treatment for refractory tremor for decades, with sustained long-term efficacy. Recently, magnetic resonance-guided high-frequency focused ultrasound (HIFU) has emerged as an alternative, prompting comparisons between these approaches. Deep brain stimulation offers long-lasting tremor control in Parkinson's disease (PD) and essential tremor (ET). In addition, it enables us to advance our understanding of brain circuits by integrating neuroimaging, electrophysiology, and connectomics data to map the best stimulation spots. Technologies such as adaptive and directional DBS enable real-time adjustments and greater precision, optimizing results and minimizing adverse effects. Although HIFU shows promising results, it remains an ablative and non-adjustable therapy, contrasting with DBS's dynamic and customizable advances.